The Construction of Masculinity in Layangan Putus - Mercillia Widodo; Jenny Mochtar (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
A phenomenal sinetron, Layangan Putus, has enraptured and polarized Indonesian audiences when it was aired. With its accessibility and popularity, sinetron is a powerful tool of the construction of identity and is a source of potent, though sometimes invisible, ideologies. The construction of masculinity is evident through four social forms of images, myths, discourses and practices proposed by Reeser (2010). The main character, Aris, is portrayed as the ideal man with his capability to provide and attract women. This notion is in full contrast with other male characters portrayed as ‘failed’ or mediocre, and whose weaknesses only showcase Aris’ dominance. The sinetron depicts the reality as Aris’ qualities are encouraged and even catapulted as the epitome of masculinity. On the other hand, his loss of masculinity in the end serves as a critique towards the idealized masuline man. This suggests the double nature of gender representations in mass media.